Changing minds about climate change in Indonesia through a TV drama - Green, Donald P.; Eko, Rosiana; Ong, Lionel; Paskuj, Benedek; Godfrey, Anna; Garg, Ankur; Rea, Helena (Frontiers in Communication, 2024)
Drama has been shown to change attitudes and inspire action on topics as diverse as health, sanitation, intergroup conflict and gender equality, but rarely have randomized trials assessed the influence of narrative entertainment programs focusing on climate change and environmental protection. We report the results of an experiment in which young Indonesian adults were sampled from five metropolitan areas. Participants were randomly assigned to watch a condensed two-hour version of a new awardwinning TV drama series #CeritaKita (Our Story) -and accompanying social media discussion program Ngobrolin #CeritaKita (Chatter -Our Story) -as opposed to a placebo drama/discussion that lacked climate and environmental content. Outcomes were assessed via survey one to seven days after exposure to the shows, and through a follow up survey after five months. We find that the treatment group became significantly more knowledgeable about environmental issues such as deforestation, an effect that persists long term. Other outcomes, such as motivation to participate in public discussion on climate change, willingness to follow influencers who post about environmental issues on social media, support for policies to address climate change and support for more media coverage of this issue, moved initially after viewing but subsided over time, possibly due to lack of continued exposure and other changes in context. This pattern of results suggests that ongoing/ seasonal programming may be needed in order to sustain attitudinal and behavioral change, draw media market investments, and change public narratives at scale when it matters most.